DESIGN BLACK SOLDIER FLY CAGES TO IMPROVE EGG PRODUCTIVITY BASED ON THE ON THE INTERNET OF THINGS - Akhdan Fadhli Zaim; Onny Setyawati; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
Maggot or Black Soldier Fly larvae is one of the living things that can be used as waste treatment technology, especially in organic waste. Factors that greatly affect the growth of BSF maggots are the feed media provided and environmental conditions. The environmental conditions referred to here are temperature, sunlight, and humidity during the life cycle of the adult fly phase inthe cage. The number of eggs produced will affect how many maggots will be produced. Processing organic waste is very dependent on the number of maggots, the more waste, the more maggots are needed. This research will present the design of fly cages that have been modified into IoT-based cages and how the characteristics of IoT devices for black soldier fly cages. The purpose of this research is to maximize the productivity of black soldier flies through technology. The results showed that the IoT-based cage design will be installed with a hose nozzle spraying mist outside the cage and a grow light lamp. Characteristics of IoT Devices using ESP32 microcontroller, DHT22 sensor to measure temperature and humidity, and TSL2561 sensor to measure Light Intensity, Actuators controlled through relays are Pump12V and Growlight T10, then data will be sent via Firebase RTDB and application. Optimal environmental conditions can increase the productivity of Black Soldier Fly. Keywords: Black Soldier Fly, Light Intensity, Egg, Temperature, Humidity, TSL2561, DHT22.